Tandem cervical and lumbar canal stenosis in an elderly woman with long-standing rheumatoid arthritis (Indian Journal of Case Reports, 2026)
Tandem spinal stenosis involving both cervical and lumbar regions is typically degenerative and may be accelerated by chronic inflammatory arthropathies such as rheumatoid arthritis (RA). We report the case of a 71-year-old woman with a 10-year history of RA who developed progressive cervical and lumbar radiculopathy due to inflammatory changes in the vertebral canal. In 2015, she developed an acute systemic illness with high-grade fever, severe joint pain, and marked swelling of the knees and wrists on both sides. She was diagnosed with RA and initiated on disease modifying anti-rheumatic drugs. From 2024 onward, she developed progressive gait imbalance, limb weakness, and neuropathic symptoms. Magnetic resonance imaging of the spine revealed multilevel degenerative spondylosis with narrowing of the vertebral canal in cervical (C4–C7) and lumbar levels (L3–L5) with disc bulges. This case highlights the cumulative impact of RA-related inflammation and age-related degeneration on the development of tandem stenosis and the challenges of management in elderly patients